2016
DOI: 10.1007/s00784-016-1974-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative oral analgesics on pulpal anesthesia in patients with irreversible pulpitis—a systematic review and meta-analysis

Abstract: When compared to placebo, preemptive oral analgesics are superior in achieving anesthetic success in inflamed pulp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
1
23
1
4
Order By: Relevance
“…, Shirvani et al . , Tupyota et al . ) reported that oral premedication with NSAIDs increased the success rate of IANB in teeth with irreversible pulpitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Shirvani et al . , Tupyota et al . ) reported that oral premedication with NSAIDs increased the success rate of IANB in teeth with irreversible pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving successful anaesthesia in mandibular molars diagnosed with irreversible pulpitis is more difficult compared to teeth with normal pulps (Modaresi et al 2006). Previous meta-analyses (Li et al 2012, Lapidus et al 2016, Corbella et al 2017, Shirvani et al 2017, Tupyota et al 2017 reported that oral premedication with NSAIDs increased the success rate of IANB in teeth with irreversible pulpitis. However, the effect of various premedication drugs could not be compared to each other as they were not studied in head-to-head trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibuprofen has been used as a preoperative medication, with the goal of decreasing intraoperative narcotics administration and improving postoperative pain control . A single randomized controlled study documents the safety and efficacy of intravenous ibuprofen during pediatric tonsillectomy .…”
Section: Introductionmentioning
confidence: 99%
“…Patient comfort, cost-saving and rationalization of care time justify the search for an alternative to emergency partial endodontic treatment. A recent systematic review by Shirvani et al [15] showed superior intraoperative analgesia for patients with irreversible pulpitis after administration of preemptive nonsteroidal anti-inflammatory drugs. But, to our knowledge, no clinical trial on the use of orally administered corticosteroid for the treatment of dental pulp inflammation has been conducted.…”
Section: Introductionmentioning
confidence: 99%